"You become one with the place": Social mixing, social capital, and the lived experience of urban desegregation in the Roma community. (October 2021) - Méreiné-Berki, Boglárka; Málovics, György; Creţan, Remus
Abstract: Policymakers are eager to create socially mixed neighbourhoods, even though evidence for the positive impact of social mixing is patchy. In this paper, we examine the relationship between social mixing, social capital, and the lived experience of residents affected by the desegregation of an urban Roma area. Using qualitative data from a participatory action research (PAR) process in Hungary, we explore the two-way relationship between desegregation and bonding, bridging, and linking forms of social capital. Our results suggest that desegregation has complex and contradictory impacts on lived experience, and that these relate to changes in social forms of capital. Our findings speak to the heterogeneity of the Roma segregated community, and to the multifaceted nature of social capital as a resource. We conclude that the presence of strong negative neighbourhood effects, acknowledged by marginalized residents themselves, indicates that social mixing can contribute to the enhancement of wellbeing and social mobility for many segregated Roma families. However, desegregation alone is insufficient, and further policies are required to increase socio-spatial integration and deal with the social, economic, and cultural causes of extreme poverty. Highlights: For segregated Roma, social mixing could simply lead to resegregation, as polarised enclaves re-formed over time. Social mixing has complex and contradictory impacts on wellbeing in segregated Roma communities, across material and non-material domains. New institutions may be needed in order to develop forms of supportive linking capital to ensure that Roma families are able to move to inclusive urban environments. Evaluation of desegregation policy needs to be institutionalized, using a wider range of indicators of wellbeing than income alone. For a nuanced position on social mixing, we propose the treatment of the segregated Roma community as heterogeneous towards social mixing.